KECEMASAN IBU HAMIL TERHADAP COVID-19 (SYSTEMATIC LITERATURE REVIEW) - Yocki Yuanti; Daniah Daniah; Nuraini Nuraini; Cindy Ria Aprilia Putri; Anastasia Susila Anugrah Ningrum (Balai Penelitian dan Pengembangan Kesehatan Baturaja, 2021)
SARS-CoV-2 is a coronavirus from the Betacoronavirus group. The COVID-19 pandemic can cause psychological effects, including stress, anxiety, and depression. Worry and anxiety during the COVID-19 pandemic in pregnant women can cause them to refrain from taking prenatal care. The purpose of this review is to analyze and review journals related to the anxiety of pregnant women about COVID-19. This research method is Systematic Literature Review by searching for journals using Google Scholar, ProQuest, PubMed, and Garuda databases from 2019 – 2021 and the literature selection process using PRISMA diagrams with a Cross Sectional research design. The results of this study are that at the initial stage, 3.197 articles were collected, then various selections were made so that the final results obtained were 5 articles that were worthy of analysis. The research topics are 3 out of 5 articles reporting mild anxiety during the COVID-19 pandemic and 2 out of 5 articles reporting severe anxiety during COVID-19. The conclusion of this review is that the anxiety of pregnant women during the COVID-19 pandemic varies so that problems related to anxiety can be immediately overcome by Antenatal Care (ANC) visits.